Alcohol-impaired driving and road safety: Examining the impact of alcohol on driving errors of Indian drivers. (January 2022) - Kumar Yadav, Ankit; Velaga, Nagendra R.
Highlights: Effects of 0.03%, 0.05%, and 0.08% BACs on driving errors of Indian drivers were analysed. 82 participants were recruited for the driving simulator experiments. Longitudinal and lateral driving error measures were examined. Significant driving error tendencies were observed at 0.03% BAC, which is the maximum legal limit for driving in India. Abstract: Driving error is an intrinsic component of unsafe driving behaviour. Even though alcohol results in substantial crash fatalities on Indian roads, there is hardly any evidence-based research on alcohol impairment in the driving errors of Indian drivers. The present study examined the effects of differentiated Blood Alcohol Concentration (BAC) levels (0%, 0.03%, 0.05%, and 0.08%) on the driving errors of Indian drivers. 82 volunteers participated in the driving simulator study and drove in rural and urban environments in a randomized and counterbalanced order. Generalized negative binomial regression models were developed for longitudinal and lateral driving error measures. Compared to the sober state, the increments in speed limit violations were 53%, 138% and 143% in rural driving environment, and 68%, 89%, 95% in urban driving environment at 0.03%, 0.05% and 0.08% BACs. While 0.03% and 0.05% BACs did not significantly influence the lane excursions in rural environment, 0.08% BAC resulted in 107% increment; corresponding increments were 71%, 84%, and 148% in urban environment. In rural environment, 0.03%, 0.05% and 0.08% BACs resulted in 28%, 39% and 58% increments in low RPM frequencies (RPM < 1000), and 76%, 95% and 106% increments in high RPM frequencies (RPM > 5000). In urban environment, the increments were 35%, 56% and 71% for low RPMs at 0.03%, 0.05% and 0.08% BACs; whereas, for high RPMs, the increments at 0.05% and 0.08% BACs were 45% and 67% respectively (no significant influence of 0.03% BAC). The study identified the significant risk factors influencing driving errors, thereby sketching the risky driving profiles.